Social Interaction of Class IV Elementary School Students During the Covid-19 Pandemic - Afriani, Mayang; Ramadan, Zaka Hadikusuma (International Journal of Elementary Education, 2021)
Students also experience the impact of Covid-19 by limiting social interaction. However, social interaction is needed for a child to build character and social skills in interacting with other people. This study aimed to analyze patterns of social interaction in the fourth grade COVID-19 period in elementary school. The research subjects were 3 teachers and 90 students. The research instruments are interviews and questionnaires. The data collection technique used in this study was non-test, namely a questionnaire (questionnaire) and interviews. The results showed that social interaction during the pandemic was less effective. As evidenced by the five indicators, working together has an average score of 82.43%; during a pandemic, it is less effective due to limitations and many obstacles. The openness of the average value of 82.43% is classified as "good," and many students still do not understand technology for online learning and how to use it—empathy, with an average value of 80.95% (good). There is already an awareness in students to empathize with their friends. Giving motivation an average value of 79.70% is classified as "good" when learning students support each other and work together in doing assignments together at home. With a positive sense of the average value of 81.56%, students can develop positive values in the surrounding environment. Similarity with others, the average value is 82.15%, there is an attitude of equality in students to their friends in working on assignments and collecting assignments. It can be concluded that students' social interactions during the current Covid-19 period are not running perfectly compared to face-to-face.